ESG Rating in Investment Risk Analysis of Companies Listed on the Public Market in Poland. (15th April 2015) - Czerwińska, Teresa; Kaźmierkiewicz, Piotr
<x xml:space="preserve">Abstract</x> This study verifies the hypothesis that greater transparency of public companies in disclosing non‐financial (ESG) data results in lower volatility of return rates on securities issued by them, thereby reducing investment portfolio risk understood as return rate volatility. Non‐financial data reporting contributes to increased transparency, predictability of companies' operations and hence to significant reduction in information asymmetry on the capital market, and ultimately considerably reduces forecasting errors in risk–return profile of investment portfolios. The research conducted has shown that there is a large information gap on the Polish market, especially as regards ESG reporting. The overall level of reporting on non‐financial data is low. In the analysed period, the shares issued by companies with higher ESG rating were distinguished by an over‐average return rate and lower return rate volatility as well as lower forecasting error in return rates, which is indicated by the standard error parameter (alpha and beta coefficients).